EFFECT OF COMBINATION OF OXYTOCIN MASSAGE AND HYPNOBREASTFEEDING ON UTERINE INVOLUTION AND PROLACTIN LEVELS IN POSTPARTUM MOTHERS - Yuni Nor Aini; Hadi Hadi; Sri Rahayu; Noor Pramono; Donny Kristanto Mulyantoro (Belitung Raya Foundation, Indonesia, 2017)
Background: The absence of contractions after childbirth can lead to a slow-running uterine involution process. Thus, the effort to maintain and accelerate the process is needed. Oxytocin massage and hypnobreastfeeding are considered as an alternative treatment, but the effect of the combination of the two treatments have not yet been examined. Objective: To examine the effect of combination of oxytocin massage and hypnobreastfeeding on uterine involution and prolactin levels in postpartum. Methods: A quasi-experimental study with pretest posttest control group design. a total of 40 respondents were recruited using simple random sampling, with 20 respondents assigned in a treatment group and a control group. Metline and ELISA methods were used to measure uterine involution prolactin levels. Paired t-test and independent t-test were used to analyze the data. Results: There was a significant decrease of uterine involution in the experiment group and control group after intervention with p-value 0.000 (<0.05), and it can be seen that the uterine involution in the experiment group (6.05) was faster than uterine involution in the control group (7.00). Findings also showed that the prolactin level in the experiment group (273.53) was higher than the prolactin level in the control group (209.37). Conclusion: There was statistically significant effect of the combination of oxytocin massage and hypnobreastfeeding on the uterine involution and prolactin level in postpartum mothers. It is expected that the combination of oxytocin massage and hypnobreastfeeding can be used as a consideration and a reference in providing postpartum midwifery care.